Self-assembled supramolecular hydrogel based on PCL-PEG-PCL triblock copolymer and γ-cyclodextrin inclusion complex for sustained delivery of dexamethasone - Khodaverdi, Elham; Gharechahi, Marzieh; Alibolandi, Mona; Tekie, Farnaz Sadat Mirzazadeh; Khashyarmanesh, Bibi Zahra; Hadizadeh, Farzin (International Journal of Pharmaceutical Investigation)
In this study, thermosensitive, water-soluble, and biodegradable triblock copolymer PCL600-PEG6000-PCL600 was used to form supramolecular hydrogel (SMGel) by inclusion complexation with γ-cyclodextrin (γ-CD). The prepared SMGel was investigated as a carrier for sustained release of dexamethasone. The triblock copolymer PCL-PEG-PCL [where PCL = polycaprolactone, PEG = poly(ethylene glycol)] was synthesized by the ring-opening polymerization method using microwave irradiation. The polymerization reaction and the copolymer structures were evaluated by nuclear magnetic resonance (NMR) and gel permeation chromatography (GPC). SMGel was prepared in aqueous solution by blending an aqueous γ-CD solution with aqueous solution of PCL-PEG-PCL triblock copolymer at room temperature. The sol-to-gel transition time was measured at various concentrations of copolymer and γ-CD. As-prepared SMGel was used to prepare a sustained, controllable drug delivery system of dexamethasone sodium phosphate. The SMGel was also characterized in terms of rheological, morphological, and structural properties. Results obtained from proton nuclear magnetic resonance (1H-NMR) and GPC demonstrated that microwave irradiation is a simple and reliable method for synthesis of PEG-PCL copolymer. The SMGel with excellent syringability was prepared by mixing of 20% wt γ-CD and 10% wt of copolymer within 4 s. The SMGel containing 10% wt copolymer, 20% wt γ-CD, and 0.5% or 0.1% wt dexamethasone released approximately 100% and 45% of drug over up to 23 days, respectively. It could be concluded that SMGel based on self-assembly of inclusion complexes between PCL-PEG-PCL copolymer and γ-CD could be used as a basis for injectable drug delivery systems that provide sustained and controlled release of macromolecular drugs such as dexamethasone.
Keywords: γ-cyclodextrin (γ-CD); dexamethasone; PEG-PCL; supramolecular hydrogel (SMGel)